THE EFFECT OF GOOD CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY ON FINANCIAL PERFORMANCE - Jennie Vania; Aminah; Haninun (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This assessment aims to examine the influence of Good Corporate Government (GCG) and Corporate Social Responsibility (CSR) structures on the financial performance of the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) in 2020-2022. Good Corporate Governance (GCG) uses measurements of Managerial Ownership, Institutional Ownership, Independent Commissioners, and Audit Committees. Measurement of Corporate Social Responsibility (CSR) using Corporate Social Responsibility Index (CSRDI). This assessment tested data in a purposive sampling  method with IBM SPSS Estimations 23. This evaluation test contains 16 companies that meet the main guidelines for listing on the Indonesia Stock Exchange 2020-2022. The analysis method uses quantitative using classical assumptions, and multiple linear analysis. Showing that the results for legitimate ownership variables, review warnings gather have little effect on the company's financial presentation, while for the Good Corporate Governance (GCG) system, independent commissioners, institutional ownership has a significant impact on the company's financial performance which is reflected in the company's return on assets (ROA). The monetary presentation (ROA) of the company is influenced by the Corporate Social Responsibility section.